Análisis de la privacidad de los datos de los usuarios, en el contexto del internet de las cosas - Coello Márquez, Mildred Vicenta (2023)
The Internet of Things has become one of the most proliferating and impactful technologies in our entire history, with assured growth projections, becoming an integral part of daily life, with devices ranging from the car connected to the Internet to the refrigerator, heart rate bracelet, home appliances, basically, everything manufactured today, has access to the Internet and the collection of user data, which has raised significant concerns about the privacy of user data when using this technology, therefore, in this research the main objective was to analyze the risks and exposure of user data privacy in the context of the Internet of Things (IoT). To carry out the analysis, the use of the bibliographic method was carried out, with which solid foundations were established through the review of important information to support the research, the analytical method was also used to interpret and analyze the information collected and serve as enrichment for the research, together with the inductive method that helped us to be able to give general conclusions from those analyzed. According to the analysis carried out, it was found that IoT devices constantly collect data about the user, including unauthorized data collection, generating privacy problems. This data is stored and processed by AIs that can organize an archetype of the user from your data and through this, be able to show you specific advertising, planned and directed especially according to your personality, generating deliberate manipulation, in addition to all this information collected can be used by other different companies for unknown purposes, violating the privacy of the user.